Hepatitis C virus‐related symptoms, but not quality of life, were improved by treatment with direct‐acting antivirals. Issue 3 (13th November 2017) - Ichikawa, Tatsuki; Miyaaki, Hisamitsu; Miuma, Satoshi; Taura, Naota; Motoyoshi, Yasuhide; Akahoshi, Hiroshi; Nakamura, Satomi; Nakamura, Junpei; Takahashi, Youichi; Honda, Tetsurou; Yajima, Hiroyuki; Uehara, Ryouhei; et al.
Abstract : Aim: Direct‐acting antivirals (DAAs) for the treatment of hepatitis C virus (HCV) infection have a significantly high sustained virologic response rate after a short treatment course and do not have any severe adverse effects. Patient‐reported outcomes (PROs) have become increasingly important to assess the total impact of a chronic disease. We aimed to evaluate the changes in symptoms of patients with HCV infection treated with DAAs by using PROs. Methods: A total of 107 patients with chronic HCV infection were treated with DAAs. Daclatasvir/asunaprevir or sofosbuvir/ledipasvir was used for HCV 1B infection, and sofosbuvir/ribavirin for HCV 2A/2B infection. The PROs measured at the start of treatment and 1 year after the start of treatment were cirrhosis‐related symptom score (CSS), presence of restless legs syndrome (RLS), Epworth sleepiness scale (ESS), Pittsburg sleep quality index (PSQI), Kessler 6 score (K‐6), and the SF‐36 to measure quality of life (QOL). All patients had a sustained virologic response rate of 24. Results: The CSS, PSQI, K‐6, and RLS scores were improved 1 year after beginning treatment. However, QOL had not recovered. Changes in total CSS were correlated with HCV genotype, sex, hypertensive drug use, serum low‐density lipoprotein, and ESS at the start of treatment and RLS 1 year after the start of treatment. The factors that contributed to worsening of CSS were HCV genotype 2B and RLS 1 year after the start of treatment. Conclusion: Treatment with DAAs eliminated HCV‐RNA and improved most symptoms, but QOL did not recover.